Composition containing metal oxide particles with reduced generation of volatile aldehydes
By controlling the alcohol ratio of 1 to 2 carbon atoms in the composition, and inhibiting the generation of volatile aldehydes under photocatalysis, the problem of the metal oxide particle composition producing volatile aldehydes under photocatalysis in the prior art is solved, and a safer and more environmentally friendly composition application is achieved.
Patent Information
- Application Number
- CN202280054717.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-16
- Filing Date
- 2022-10-14
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-10-14
AI Technical Summary
In the prior art, compositions containing metal oxide particles are prone to produce volatile aldehyde compounds under photocatalysis, resulting in environmental pollution and health risks.
A composition containing photoactive metal oxide particles, a dispersant and an organic solvent was developed, and the alcohol ratio of 1 to 2 carbon atoms in the composition was controlled below 200 ppm to inhibit the generation of volatile aldehydes under photocatalytic action.
Through the use of this composition, the concentration of volatile aldehyde compounds generated under photocatalysis can be significantly reduced, reaching less than 2 ppm, reducing environmental pollution and health risks.
Smart Images

Figure FDA0005272058120000031 
Figure GDA0004698738750000041 
Figure GDA0004698738750000042
Abstract
Description
Technical Field
[0001] The present invention relates to a composition containing metal oxide particles with reduced generation of volatile aldehydes and a method for producing the same. Background Art
[0002] In the field of coating of resins, films, etc., a composition containing a solvent and containing metal oxide particles is used.
[0003] In addition, regarding metal oxide particles, a large number of particles having photoactivity have been reported. Titanium oxide particles, tin oxide particles, and zirconium oxide particles are representative examples of particles having photoactivity.
[0004] Disclosed are a modified metal oxide colloidal particle (C) and a coating composition using the modified metal oxide colloidal particle (C). The modified metal oxide colloidal particle (C) is a modified metal oxide colloidal particle having a metal oxide colloidal particle as a core and its outer surface coated with a composite oxide colloidal particle. The modified metal oxide colloidal particle (C) is a modified metal oxide colloidal particle having a metal oxide colloidal particle as a core and its outer surface coated with a silica-tin oxide composite oxide colloidal particle (B) having a primary particle size of 1 to 4 nm by combining an amine compound with a mass ratio of silica to tin oxide of 0.1 to 5.0 and a molar ratio of M / (SnO2+SiO2) (wherein M represents an amine compound) of 0.001 to 0.08 (see Patent Document 1).
[0005] A method for producing nanoparticles is disclosed, characterized in that the surface of nanoparticles of metal or metal oxide is coated with a phosphoric acid-based surfactant (see Patent Document 2).
[0006] A titanium oxide dispersion is disclosed, which contains titanium oxide particles coated with an oxyacid containing phosphorus, a (meth)acrylic acid-based monomer, and an oxyacid of phosphorus or sulfur (see Patent Document 3).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. WO2011 / 090084 Pamphlet
[0010] Patent Document 2: Japanese Patent Application Laid-Open No. 2010-159464
[0011] Patent Document 3: Japanese Patent Application Laid-Open No. 2011-074328 Summary of the invention
[0012] Problems to be solved by the invention
[0013] The present invention provides a composition containing photoactive metal oxide particles and suppressing the generation of aldehyde compounds and the like even by photocatalytic action, and a method for producing the same.
[0014] Means for solving problems
[0015] According to a first aspect of the present invention, there is provided a composition comprising photoactive metal oxide particles (A), a dispersant (B), and an organic solvent (C) other than a volatile aldehyde compound, wherein the alcohol having 1 to 2 carbon atoms is contained in the composition in a proportion of 200 ppm or less.
[0016] According to a second aspect, in the composition according to the first aspect, the photoactive metal oxide particles (A) are metal oxide particles containing at least one photoactive metal oxide selected from titanium oxide, tin oxide, and zirconium oxide, and having an average particle size of 5 to 500 nm as measured by a dynamic light scattering method,
[0017] As a third aspect, in the composition according to the first aspect or the second aspect, the photoactive metal oxide particles (A) contain 50 mol % or more of at least one photoactive metal oxide selected from titanium oxide, tin oxide, and zirconium oxide in all metal oxides,
[0018] According to a fourth aspect, the composition according to any one of the first to third aspects, wherein the photoactive metal oxide particles (A) are metal oxide particles formed of a photoactive metal oxide, metal oxide particles containing a photoactive metal oxide, or core-shell type metal oxide particles, wherein the core-shell type metal oxide particles are core-shell type metal oxide particles in which the surface of a metal oxide particle to be a core is coated with a coating layer of metal oxide particles having a metal oxide component or a metal oxide content different from that of the metal oxide of the core, and the metal oxide particles of the core, the metal oxide particles of the coating layer, or both contain a photoactive metal oxide,
[0019] According to a fifth aspect, the composition according to the fourth aspect, wherein the photoactive metal oxide particles (A) are core-shell type metal oxide particles in which the surfaces of metal oxide particles containing titanium oxide serving as cores are coated with metal oxide particles containing silicon dioxide, and the metal oxide contains 50 mol % or more of titanium oxide in the total metal oxides.
[0020] As a sixth aspect, in the composition according to the fourth aspect, the metal oxide particles of the core are particles of titanium oxide, zirconium oxide, tin oxide, a composite oxide of titanium oxide-tin oxide, a composite oxide of zirconium oxide-tin oxide, a composite oxide of titanium oxide-zirconium oxide, or a composite oxide of titanium oxide-zirconium oxide-tin oxide,
[0021] As a seventh aspect, in the composition according to the fourth aspect, the metal oxide particles of the coating layer are metal oxide particles or composite metal oxide particles of at least one selected from silicon dioxide, tin oxide, antimony oxide, tungsten oxide, aluminum oxide, and zirconium oxide,
[0022] According to an eighth aspect, in the composition according to any one of the first to seventh aspects, the dispersant (B) is a silane compound, an organic acid or a salt thereof, a phosphoric acid ester, or a surfactant.
[0023] According to a ninth aspect, in the composition according to the eighth aspect, the silane compound is a silane coupling agent, and the silane coupling agent is at least one silane compound selected from the group consisting of formula (1) to formula (3).
[0024] R 1 a Si(R 2 ) 4-a Formula (1)
[0025] 〔R 3 b Si(R 4 ) 3-b 〕2Y c Formula (2)
[0026] R 5 d Si(R 6 ) 4-d Formula (3)
[0027] (In formula (1), R 1 Each of R is an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having a polyether group, an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a urea group, or a cyano group. 1 Combined with silicon atoms by Si-C bonds, R 2 Each represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer of 1 to 3.
[0028] In formula (2) and formula (3), R 3 and R 5 Each of them is an alkyl group having 1 to 3 carbon atoms or an aryl group having 6 to 30 carbon atoms, and R 3 and R 5 Each is bonded to the silicon atom by Si-C bond, R4 and R 6 Each represents an alkoxy group, an acyloxy group, or a halogen group, Y represents an alkylene group, an NH group, or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3.
[0029] As a tenth aspect, the composition according to the eighth aspect, wherein the organic acid is at least one organic acid selected from the group consisting of dibasic aliphatic carboxylic acids, aliphatic hydroxycarboxylic acids, amino acids, and chelating agents, the dibasic aliphatic carboxylic acids are selected from the group consisting of oxalic acid, malonic acid, and succinic acid, the aliphatic hydroxycarboxylic acids are selected from the group consisting of glycolic acid, lactic acid, malic acid, tartaric acid, and citric acid, the amino acids are selected from the group consisting of glycine, alanine, valine, leucine, serine, and threonine, and the chelating agent is selected from the group consisting of ethylenediaminetetraacetic acid, L-aspartic acid-N,N-diacetic acid, and diethylenetriaminepentaacetic acid,
[0030] According to an eleventh aspect, in the composition according to the eighth aspect, the phosphate ester is at least one phosphate ester selected from the group consisting of formula (4) to formula (6),
[0031]
[0032]
[0033]
[0034] (In formulae (4) to (6), X1, X2, and X3 each represent an alkylene group having 2 to 20 carbon atoms, f, h, and j each represent an integer from 1 to 100, e, g, and i each represent an integer from 1 to 3, and Y1, Y2, and Y3 each represent a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, or a (meth)acryloyl group.)
[0035] According to a twelfth aspect, in the composition according to the eighth aspect, the phosphate ester is a polyoxyethylene alkyl (C6-10) ether phosphate ester having an alkyl group having 6 to 10 carbon atoms,
[0036] According to a 13th aspect, in the composition according to the 8th aspect, the surfactant is an anionic surfactant, a cationic surfactant, a nonionic surfactant, or an amphoteric surfactant.
[0037] According to a fourteenth aspect, in the composition according to any one of the first to thirteenth aspects, the organic solvent (C) is an alcohol, ester, ketone, amide, or hydrocarbon having 3 to 10 carbon atoms and optionally having an ether bond.
[0038] According to a fifteenth aspect, the composition according to any one of the first aspect to the fourteenth aspect further comprises a secondary or tertiary amine having a total carbon number of 5 to 35.
[0039] According to a sixteenth aspect, the composition according to any one of the first aspect to the fifteenth aspect is provided at 0.4 mW / cm 2 When 15 g of the above composition is irradiated with ultraviolet light of a wavelength of 365 nm for 4 hours, the volatile aldehyde compound generated in the composition is 2 ppm or less,
[0040] As a 17th aspect, it is a composition according to any one of the 1st aspect to the 16th aspect, wherein the solid content is 0.1 to 70 mass %, and the photoactive metal oxide particles (A) are 80 to 99 mass % in the total solid content, and the dispersant (B) is 1 to 20 mass %,
[0041] According to an eighteenth aspect, the present invention provides a varnish comprising the composition according to any one of the first aspect to the seventeenth aspect, further comprising a thermosetting or photocurable resin.
[0042] As a 19th aspect, the varnish according to the 18th aspect is provided, wherein the varnish is a hard coating agent or a filler, and
[0043] According to a 20th aspect, there is provided a method for producing a composition according to any one of the first aspect to the seventeenth aspect, comprising the following steps (i) and (ii):
[0044] Step (i): a step of mixing photoactive metal oxide particles (A), a dispersant (B), and an organic solvent (C) other than a volatile aldehyde compound,
[0045] Step (ii): a step (ii) of removing the alcohol having 1 to 2 carbon atoms in the liquid obtained in step (i) until the alcohol having 1 to 2 carbon atoms is contained in the entire solvent in a proportion of 200 ppm or less.
[0046] Effects of the Invention
[0047] Regarding photoactive metal oxide particles, for example, metal oxide particles containing titanium oxide, tin oxide, and zirconium oxide, titanium oxide, tin oxide, and zirconium oxide have a photocatalytic effect, and have the effect of reducing themselves and oxidizing others. For a composition containing photoactive metal oxide particles, the photoactive metal oxide particles are dispersed in a solvent. As a solvent, low-level alcohols having 1 to 2 carbon atoms, such as methanol and ethanol, are generally used. These alcohols are oxidized to formaldehyde by the photocatalytic action of the photoactive metal oxide particles, and ethanol is oxidized to acetaldehyde. It is known that these formaldehyde and acetaldehyde are volatile aldehyde compounds that have adverse effects on the human body, and it is required to reduce their production as much as possible.
[0048] The composition containing photoactive metal oxide particles may contain a dispersant or an optional additive. These dispersants and additives may be mixed into the final product of the dispersants and additives by using lower alcohols as raw materials or reaction solvents during their production process.
[0049] In addition, in the production of compositions containing photoactive metal oxide particles, methanol and ethanol are sometimes mixed as byproducts (e.g., hydrolysis residues of silane coupling agents) from reactions in the product manufacturing process, or are used as cleaning solvents in kettles and pipes in manufacturing equipment and remain and are mixed into the above-mentioned compositions. Since these compositions contain methanol and ethanol, formaldehyde and acetaldehyde are generated by the photocatalytic action of the photoactive metal oxide particles.
[0050] It is known that the composition of the present invention contains an organic solvent other than a volatile aldehyde compound, and the alcohol having 1 to 2 carbon atoms contained in the composition is contained in a ratio of 200 ppm or less, so that the generation of volatile aldehydes is reduced to 2 ppm or less even by irradiation with visible light or ultraviolet light. Furthermore, when the photoactive metal oxide particles are dispersed in these organic solvents, a specific amount of a specific dispersant such as a silane coupling agent, an organic acid or a salt thereof, a phosphoric acid ester, or a surfactant is contained, so that a composition having photoactive metal oxide particles with high dispersibility is obtained. DETAILED DESCRIPTION
[0051] The present invention is a composition comprising photoactive metal oxide particles (A), a dispersant (B), and an organic solvent (C) other than a volatile aldehyde compound, wherein the alcohol having 1 to 2 carbon atoms contained in the composition is contained in an amount of 200 ppm or less. The alcohol having 1 to 2 carbon atoms contained in the composition is preferably contained in an amount of, for example, 0.001 to 200 ppm, or 0.01 to 100 ppm.
[0052] The photoactive metal oxide particles (A) may be metal oxide particles containing at least one photoactive metal oxide selected from titanium oxide, tin oxide, and zirconium oxide, and having an average particle size of 5 to 500 nm, 5 to 300 nm, 5 to 250 nm, or 5 to 60 nm as measured by dynamic light scattering.
[0053] The photoactive metal oxide particles (A) have the function of reducing themselves and oxidizing others by photocatalysis, and therefore oxidize the solvent (e.g., alcohol having 1 to 2 carbon atoms, i.e., methanol and ethanol) in the composition to generate volatile aldehydes (e.g., formaldehyde and acetaldehyde), and the ratio of the photoactive metal oxide in the total metal oxides may be 50 mol% or more, or 50 to 100 mol%. That is, the photoactive metal oxide particles (A) may contain 50 mol% or more of at least one photoactive metal oxide selected from titanium oxide, tin oxide, and zirconium oxide in the total metal oxides.
[0054] The photoactive metal oxide particles (A) may be metal oxide particles formed of a photoactive metal oxide, metal oxide particles containing a photoactive metal oxide, or core-shell type metal oxide particles.
[0055] The core-shell type metal oxide particles may be core-shell type metal oxide particles in which the surface of the metal oxide particle to be the core is coated with a coating layer of metal oxide particles having a metal oxide component or metal oxide content different from that of the metal oxide of the core, and the metal oxide particles of the core, the metal oxide particles of the coating layer, or both contain a photoactive metal oxide.
[0056] In the present specification, the photoactive metal oxide contained in the photoactive metal oxide particle (A) may be in the form of a particle or an aggregate thereof (photoactive metal oxide particle (i)). That is, the photoactive metal oxide particle (A) may be a metal oxide particle formed of the photoactive metal oxide particle (i), or a metal oxide particle containing the photoactive metal oxide particle (i). In addition, when the photoactive metal oxide particle (A) is a core-shell type metal oxide particle, it may be a core metal oxide particle, a coating metal oxide particle, or a particle containing the photoactive metal oxide particle (i) in both forms.
[0057] The metal oxide particles formed of a photoactive metal oxide refer to the case where 100 mol % of the metal oxide particles (A) are formed only of a photoactive metal oxide (or a photoactive metal oxide particle (i)).
[0058] The metal oxide particles containing photoactive metal oxide particles refer to the case where the metal oxide particles (A) contain photoactive metal oxides (or photoactive metal oxide particles (i)) in a ratio of 50 mol % or more and less than 100 mol % in all metal oxides.
[0059] The core-shell type metal oxide particles in which the surface of the metal oxide particle to be the core is coated with a coating layer of a metal oxide particle having a metal oxide component or a metal oxide content different from the metal oxide component or the metal oxide content of the metal oxide of the core are the case where the metal oxide particles of the core, the metal oxide particles of the coating layer, or both contain a photoactive metal oxide (or photoactive metal oxide particles (i)) in a ratio of 50 mol% or more and 100 mol% or less in all metal oxides.
[0060] For example, the photoactive metal oxide particles (A) are core-shell type metal oxide particles in which the surface of metal oxide particles containing titanium oxide as a core is coated with metal oxide particles containing silicon dioxide, and the particles contain 50 mol % or more of titanium oxide in the total metal oxide.
[0061] For example, the metal oxide particles used in the core may include particles containing titanium oxide, zirconium oxide, tin oxide, titanium oxide-tin oxide composite oxide, zirconium oxide-tin oxide composite oxide, titanium oxide-zirconium oxide composite oxide, or titanium oxide-zirconium oxide-tin oxide composite oxide. These particles have an average primary particle size of 5 to 500 nm, 5 to 300 nm, 5 to 250 nm, or 5 to 60 nm as observed by a transmission electron microscope.
[0062] For example, as the metal oxide particles contained in the coating layer, at least one metal oxide particle or composite metal oxide particle selected from silicon dioxide, tin oxide, antimony oxide, tungsten oxide, aluminum oxide, and zirconium oxide can be exemplified. They have an average primary particle size of 1 to 10 nm, or 1 to 5 nm by observation under a transmission electron microscope. As the metal oxide particles contained in the coating layer, metal oxide particles in which silicon dioxide, tin oxide, antimony oxide, tungsten oxide, aluminum oxide, and zirconium oxide exist alone, or composite metal oxide particles formed by combining a plurality of the above metal oxides. As composite metal oxide particles, composite metal oxide particles of tin oxide-silicon dioxide, composite metal oxide particles of tin oxide-zirconium oxide-silicon dioxide, composite metal oxide particles of tin oxide-tungsten oxide-silicon dioxide, composite metal oxide particles of antimony oxide-silicon dioxide, etc. can be cited. In the case where the metal oxide particles of the coating layer include silicon dioxide particles, the ratio of silicon dioxide particles to other metal oxide particles can be set to a ratio of 0.1 to 5.0 in terms of the mass ratio of (silicon dioxide) / (other metal oxides).
[0063] In the case of using a core-shell structure, the so-called coating with a coating layer containing metal oxide particles having a metal oxide component or metal oxide content different from that of the metal oxide of the core may include a case where the components of the metal oxides of the core and the coating are different, and a case where the mixing ratio of the metal oxides is different even if the components of the metal oxides of the core and the coating are partially repeated.
[0064] In the case of a core-shell structure, the mass ratio of the metal oxide particles of the core to the metal oxide particles of the coating layer can be set to the range of (coating metal oxide particles) / (core metal oxide particles)=0.05 to 0.50.
[0065] For example, when a composite oxide of tin oxide-silicon dioxide contained in the metal oxide particles of the coating layer is used as an example, sodium stannate or potassium stannate can be used as the alkali metal stannate, and sodium stannate is preferred.
[0066] As the alkali metal silicate, sodium silicate or potassium silicate can be used.
[0067] Alkali metal stannate and alkali metal silicate are prepared as an aqueous solution containing silicon dioxide / tin oxide at a mass ratio of 0.1 to 5, and then cations present in the aqueous solution are removed by a cation exchange resin.
[0068] The alkali metal stannate and alkali metal silicate are weighed so that the mass ratio of silicon dioxide to tin oxide becomes 0.1 to 5.0 and dissolved in water for preparation. The solid content concentration of the aqueous solution is preferably 1 to 12% by mass in terms of (SnO2+SiO2).
[0069] The prepared aqueous solution is subjected to cation exchange resin to remove cations. As the cation exchange resin, a hydrogen-type strongly acidic cation exchange resin is preferred, and the cation exchange can be performed using a column filled with, for example, Anvarite (trade name) 120B. By performing the cation exchange, the silicate component and the stannic acid component can be polymerized to generate silica-tin oxide composite colloidal particles having a primary particle size of 1 to 4 nm.
[0070] The silica-tin oxide composite colloidal particles lack stability and gel after several hours of standing. Therefore, it is necessary to add an amine compound immediately after cation exchange to stabilize them, and to prepare an aqueous sol of silica-tin oxide composite oxide colloidal particles having a primary particle size of 1 to 4 nm, wherein the silica / tin oxide mass ratio is 0.1 to 5.0 and the amine compound is present at a molar ratio of M / (SnO2+SiO2) (wherein M represents an amine compound) of 0.1 to 1.0. The obtained aqueous sol is 0.1 to 10% by mass in terms of (SnO2+SiO2).
[0071] In stabilizing the silica-tin oxide composite colloidal particles generated by the above-mentioned cation exchange, it is appropriate to add an amine compound in an amount of 0.1 to 1.0 as a molar ratio of M / (SnO2+SiO2) (where M represents an amine compound). The addition of an amine compound with a molar ratio of M / (SnO2+SiO2) of less than 0.1 is not preferred because it loses stability and gels after being left for several hours.
[0072] Next, an aqueous sol of metal oxide colloidal particles (a) used as a core having a primary particle size of 5 to 60 nm and an aqueous sol of silica-tin oxide composite oxide colloidal particles (b) having a primary particle size of 1 to 4 nm, which are stabilized by an amine compound with a silica / tin oxide mass ratio of 0.1 to 5.0 and a molar ratio of M / (SnO2+SiO2) (wherein M represents an amine compound) of 0.1 to 1.0, are mixed in a ratio of (b) / (a) of 0.05 to 0.50 for the mass ratio of the above-mentioned silica-tin oxide composite oxide colloidal particles to the above-mentioned metal oxide colloidal particles, thereby obtaining an aqueous sol of modified metal oxide colloidal particles (A) in which the above-mentioned metal oxide colloidal particles (a) are coated with the above-mentioned silica-tin oxide composite oxide colloidal particles (b).
[0073] The solid content concentration of the aqueous sol of the metal oxide colloidal particles (a) is 0.5 to 50% by mass, preferably 5 to 30% by mass.
[0074] The aqueous sol of the metal oxide colloidal particles (a) can be used at pH 5 to 11.5, preferably pH 7 to 11.5. The pH of the aqueous sol can be adjusted by an alkali component as needed, and examples of the alkali component include alkali metal hydroxides such as lithium, sodium, and potassium, hydroxides of alkaline earth metals such as calcium, magnesium, and strontium, alkylamines such as ammonia, ethylamine, triethylamine, isopropylamine, and n-propylamine, arylalkylamines such as benzylamine, alicyclic amines such as piperidine, alkanolamines such as monoethanolamine and triethanolamine, and quaternary ammonium hydroxide.
[0075] The mixing of the aqueous sol of the metal oxide colloidal particles (a) and the aqueous sol of the coated particles (b) is preferably performed under stirring.
[0076] The mixing ratio of the silica-tin oxide composite oxide colloidal particles (b) to the metal oxide colloidal particles (a) is preferably 0.05 to 0.50 in terms of mass ratio (b) / (a). If it is less than 0.05, the metal oxide colloidal particles (a) serving as cores cannot be sufficiently coated with the silica-tin oxide composite oxide colloidal particles (b), and a stable hydrophilic organic solvent dispersion sol or a hydrophobic organic solvent dispersion sol having a water solubility of 0.05 to 12% by mass cannot be obtained. In addition, the mass ratio is sufficiently 0.50, and even if it exceeds 0.50, it is not efficient.
[0077] Next, the obtained aqueous sol of modified metal oxide colloidal particles (A) is subjected to cation exchange. For the cation exchange, a hydrogen-type strongly acidic cation exchange resin is preferably used.
[0078] Next, an amine compound is added to the obtained aqueous sol in an amount such that the molar ratio M / (SnO2+SiO2) (wherein M represents an amine compound) relative to the above-mentioned silica-tin oxide composite oxide colloidal particles (b) is 0.001 to 0.08. If the amount of the amine compound added is less than 0.001, the dispersion stability of the hydrophilic organic solvent dispersion sol of the present invention becomes insufficient, which is not preferred. In addition, when the molar ratio of M / (SnO2+SiO2) exceeds 0.08, when the silane compound bonded to the particle surface of the above-mentioned modified metal oxide colloidal particles (A) is bonded, it may hinder the bonding.
[0079] The aqueous medium of the obtained aqueous sol is then replaced with a hydrophilic organic solvent. The dispersion medium may be replaced from water to a hydrophilic organic solvent by a known method, such as evaporation replacement under normal pressure or reduced pressure, ultrafiltration membrane method, solvent extraction method, and the like.
[0080] In order to efficiently carry out solvent replacement, the obtained aqueous sol is preferably pre-concentrated so that the concentration of the modified metal oxide colloidal particles (A) contained therein is in the range of 1 to 70% by mass, or 10 to 50% by mass. The concentration of the sol can be carried out using known methods such as heating evaporation and ultrafiltration. The temperature of the sol during solvent replacement is in the range from room temperature to the boiling point of the hydrophilic solvent. The solvent replacement is carried out until the water content in the sol becomes less than 5% by mass. The solid content concentration of the obtained sol is 20 to 70% by mass based on the total metal oxide concentration of the above-mentioned modified metal oxide colloidal particles (A).
[0081] In the present invention, an organic solvent that is replaced by a solvent can be used as the organic solvent (C) of the present invention. The organic solvent (C) is preferably an organic solvent (C) other than a volatile aldehyde compound and containing an alcohol having 1 to 2 carbon atoms in the total solvent at a ratio of 200 ppm or less. Examples of the organic solvent (C) include alcohols having 3 to 10 carbon atoms, esters, ketones, amides or hydrocarbons that may have an ether bond.
[0082] Examples of the alcohol having 3 to 10 carbon atoms include n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, ethylene glycol, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monopropyl ether.
[0083] Examples of the ketone include linear or cyclic aliphatic ketones having 3 to 30 carbon atoms, such as methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, diisopropyl ketone, diisobutyl ketone, methyl amyl ketone, and cyclohexanone.
[0084] Examples of the ether include linear or cyclic aliphatic ethers having 3 to 30 carbon atoms, such as diethyl ether and tetrahydrofuran.
[0085] Examples of esters include linear or cyclic esters having 2 to 30 carbon atoms, such as ethyl acetate, n-butyl acetate, sec-butyl acetate, methoxybutyl acetate, amyl acetate, n-propyl acetate, isopropyl acetate, ethyl lactate, butyl lactate, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, phenyl acetate, phenyl lactate, phenyl propionate, etc. Amides are aliphatic amides having 3 to 30 carbon atoms, such as dimethylacetamide, dimethylformamide, N-methylpyrrolidone, N-ethylpyrrolidone, etc.
[0086] Examples of the hydrocarbon include linear or cyclic aliphatic or aromatic hydrocarbons having 6 to 30 carbon atoms, such as hexane, heptane, octane, nonane, decane, benzene, toluene, and xylene.
[0087] The composition of the present invention may further contain a secondary or tertiary amine having a total carbon number of 5 to 35.
[0088] For example, when the photoactive metal oxide particles (A) include silica particles, the content of the amine can be set to 0.01 to 10.0 mmol, or 0.01 to 5.0 mmol, relative to 100 g of SiO 2 in the silica particles.
[0089] Examples of the secondary amine include ethyl-n-propylamine, ethyl-isopropylamine, dipropylamine, diisopropylamine, ethyl-butylamine, n-propyl-butylamine, dibutylamine, ethyl-pentylamine, n-propyl-pentylamine, isopropyl-pentylamine, dipentylamine, ethyl-octylamine, isopropyl-octylamine, butyl-octylamine, and dioctylamine.
[0090] Examples of the tertiary amine include triethylamine, ethyldi-n-propylamine, diethyl-n-propylamine, tri-n-propylamine, triisopropylamine, ethyldibutylamine, diethylbutylamine, isopropyldibutylamine, diisopropylethylamine, diisopropylbutylamine, tributylamine, ethyldipentylamine, diethylpentylamine, tripentylamine, methyldioctylamine, dimethyloctylamine, ethyldioctylamine, diethyloctylamine, trioctylamine, benzyldibutylamine, and diazabicycloundecene.
[0091] Among the above amines, secondary amines and tertiary amines having an alkyl group having 6 to 35 carbon atoms in total are preferred, and examples thereof include diisopropylamine, tripentylamine, triisopropylamine, dimethyloctylamine, and trioctylamine.
[0092] The composition of the present invention may use a silane compound, an organic acid or a salt thereof, a phosphoric acid ester, or a surfactant as the dispersant (B).
[0093] Examples of the silane compound include silane coupling agents, and examples of the silane coupling agent include at least one silane compound selected from the group consisting of Formulae (1) to (3). In the present invention, photoactive metal oxide particles (A) coated with the hydrolyzate of the above silane compound can be used.
[0094] At least one silane compound selected from the group consisting of formulae (1) to (3) may be added to the obtained hydrophilic organic solvent-dispersed sol to carry out hydrolysis, and the photoactive metal oxide particles (A) in the sol may be coated with the hydrolyzate.
[0095] In formula (1), R 1 Each of R is an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having a polyether group, an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a urea group, or a cyano group. 1 Combined with silicon atoms by Si-C bonds, and R 2 Each represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer of 1 to 3.
[0096] In formula (2) and formula (3), R 3 and R 5 Each of them is an alkyl group having 1 to 3 carbon atoms or an aryl group having 6 to 30 carbon atoms, and R 3 and R 5 Each is bonded to the silicon atom by Si-C bond, R 4 and R6 Each represents an alkoxy group, an acyloxy group, or a halogen group, Y represents an alkylene group, an NH group, or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3.
[0097] Examples of the alkyl group include alkyl groups having 1 to 18 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, 1-methyl-cyclopropyl, 2-methyl-cyclopropyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2-methyl-cyclobutyl, 3-methyl-cyclobutyl Butyl, 1,2-dimethyl-cyclopropyl, 2,3-dimethyl-cyclopropyl, 1-ethyl-cyclopropyl, 2-ethyl-cyclopropyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl , 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3-dimethyl-cyclobutyl, 2,4-dimethyl-cyclobutyl, 3,3-dimethyl-cyclobutyl, 1-n-propyl-cyclopropyl, 2-n-propyl The invention also includes, but is not limited to, 1-ethyl-2-methyl-cyclopropyl, 1-isopropyl-cyclopropyl, 2-isopropyl-cyclopropyl, 1,2,2-trimethyl-cyclopropyl, 1,2,3-trimethyl-cyclopropyl, 2,2,3-trimethyl-cyclopropyl, 1-ethyl-2-methyl-cyclopropyl, 2-ethyl-1-methyl-cyclopropyl, 2-ethyl-2-methyl-cyclopropyl and 2-ethyl-3-methyl-cyclopropyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl and octadecyl.
[0098] In addition, examples of the alkylene group include alkylene groups derived from the above-mentioned alkyl groups.
[0099] Examples of the aryl group include aryl groups having 6 to 30 carbon atoms, such as phenyl, naphthyl, anthracenyl, and pyrenyl.
[0100] Examples of the alkenyl group include alkenyl groups having 2 to 10 carbon atoms, such as vinyl, 1-propenyl, 2-propenyl, 1-methyl-1-vinyl, 1-butenyl, 2-butenyl, 3-butenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-ethylvinyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-n-propylvinyl, 1-methyl-1-butenyl, 1-methyl-2-butenyl, 1-methyl-3-butenyl, 2-ethyl-2-propenyl, 2-methyl-1-butenyl, 2-methyl-2-butenyl, 2-methyl- 3-butenyl, 3-methyl-1-butenyl, 3-methyl-2-butenyl, 3-methyl-3-butenyl, 1,1-dimethyl-2-propenyl, 1-isopropylvinyl, 1,2-dimethyl-1-propenyl, 1,2-dimethyl-2-propenyl, 1-cyclopentenyl, 2-cyclopentenyl, 3-cyclopentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, 5-hexenyl, 1-methyl-1-pentenyl, 1-methyl-2-pentenyl, 1-methyl-3-pentenyl, 1-methyl-4-pentenyl, 1-n-butylvinyl, 2-methyl-1-pentenyl, 2-methyl-2-pentenyl, etc., but are not limited to these.
[0101] Examples of the alkoxy group include alkoxy groups having 1 to 10 carbon atoms, such as a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, an isobutoxy group, a sec-butoxy group, a tert-butoxy group, an n-pentyloxy group, a 1-methyl-n-butoxy group, a 2-methyl-n-butoxy group, a 3-methyl-n-butoxy group, a 1,1-dimethyl-n-propoxy group, a 1,2-dimethyl-n-propoxy group, a 2,2-dimethyl-n-propoxy group, a 1-ethyl-n-propoxy group, and an n-hexyloxy group.
[0102] Examples of the acyloxy group include acyloxy groups having 2 to 10 carbon atoms, such as methylcarbonyloxy, ethylcarbonyloxy, n-propylcarbonyloxy, isopropylcarbonyloxy, n-butylcarbonyloxy, isobutylcarbonyloxy, sec-butylcarbonyloxy, tert-butylcarbonyloxy, n-pentylcarbonyloxy, 1-methyl-n-butylcarbonyloxy, 2-methyl-n-butylcarbonyloxy, 3-methyl-n-butylcarbonyloxy, 1,1-dimethyl-n-propylcarbonyloxy, 1,2-dimethyl-n-propylcarbonyloxy, 2,2-dimethyl-n-propylcarbonyloxy, 1-ethyl-n-propylcarbonyloxy, n-hexylcarbonyloxy, 1-methyl-n-pentylcarbonyloxy, and 2-methyl-n-pentylcarbonyloxy.
[0103] Examples of the halogen group include fluorine, chlorine, bromine, and iodine.
[0104] As the organic group having a polyether group, a polyether propyl group having an alkoxy group can be mentioned. For example, (CH3O)3SiC3H6(OC2H4)nOCH3 can be mentioned. n can be used in the range of 1 to 100, or 1 to 10.
[0105] Examples of the organic group having an epoxy group include a 2-(3,4-epoxycyclohexyl)ethyl group and a 3-glycidoxypropyl group.
[0106] The (meth)acryloyl group mentioned above means both an acryloyl group and a methacryloyl group. Examples of the organic group having a (meth)acryloyl group include a 3-methacryloyloxypropyl group and a 3-acryloyloxypropyl group.
[0107] Examples of the organic group having a mercapto group include a 3-mercaptopropyl group.
[0108] Examples of the organic group having an amino group include a 2-aminoethyl group, a 3-aminopropyl group, an N-2-(aminoethyl)-3-aminopropyl group, an N-(1,3-dimethylbutylene)aminopropyl group, an N-phenyl-3-aminopropyl group, and an N-(vinylbenzyl)-2-aminoethyl-3-aminopropyl group.
[0109] Examples of the organic group having a ureido group include a 3-ureidopropyl group.
[0110] Examples of the organic group having a cyano group include a 3-cyanopropyl group.
[0111] The silane compounds represented by the above formula (2) and formula (3) are preferably compounds that can form a trimethylsilyl group on the surface of silica particles.
[0112] Examples of these compounds include the following.
[0113]
[0114] In the above formula, R 12 The alkoxy group includes, for example, a methoxy group and an ethoxy group. As the silane compound, a silane compound manufactured by Shin-Etsu Chemical Co., Ltd. can be used.
[0115] The hydroxyl groups on the surface of the silica particles, for example, the silanol groups in the case of silica particles, can react with the above-mentioned silane compound to coat the surface of the silica particles with the above-mentioned silane compound through siloxane bonds. The reaction can be carried out at a temperature ranging from 20°C to the boiling point of the dispersion medium, for example, at a temperature ranging from 20°C to 100°C. The reaction can be carried out for about 0.1 to 6 hours.
[0116] The silane compound can cover the surface of the silica particles in an amount corresponding to 0.1 silicon atoms / nm. 2 ~6.0 / nm 2 The silane compound in a coating amount of 100 Å to 200 Å is added to the silica sol to coat the surfaces of the silica particles.
[0117] Water is required for the hydrolysis of the above-mentioned silane compound. If it is a sol of an aqueous solvent, the water in the aqueous solvent is used. When the aqueous medium solvent is replaced with an organic solvent (C), the water remaining in the solvent can also be used. For example, 0.01 to 1% by mass of water in the solvent can be used. In addition, the hydrolysis can be carried out using a catalyst or without a catalyst.
[0118] The case where the hydrolysis is carried out without a catalyst is when the surface of the silica particles is on the acidic side. When a catalyst is used, examples of the hydrolysis catalyst include metal chelates, organic acids, inorganic acids, organic bases, and inorganic bases.
[0119] Examples of metal chelates as hydrolysis catalysts include triethoxy mono(acetylacetonate)titanium and triethoxy mono(acetylacetonate)zirconium. Examples of organic acids as hydrolysis catalysts include acetic acid and oxalic acid. Examples of inorganic acids as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, phosphoric acid, etc. Examples of organic bases as hydrolysis catalysts include pyridine, pyrrole, piperazine, and quaternary ammonium salts. Examples of inorganic bases as hydrolysis catalysts include ammonia, sodium hydroxide, and potassium hydroxide.
[0120] As the organic acid, at least one organic acid selected from dibasic aliphatic carboxylic acids, aliphatic hydroxycarboxylic acids, amino acids, and chelating agents may be used. As dibasic aliphatic carboxylic acids, oxalic acid, malonic acid, and succinic acid may be mentioned. As aliphatic hydroxycarboxylic acids, glycolic acid, lactic acid, malic acid, tartaric acid, and citric acid may be mentioned. As amino acids, glycine, alanine, valine, leucine, serine, and threonine may be mentioned. As chelating agents, ethylenediaminetetraacetic acid, L-aspartic acid-N,N-diacetic acid, and diethylenetriaminepentaacetic acid may be mentioned. As organic acid salts, alkali metal salts, ammonium salts, and amine salts of the above organic acids may be mentioned. As alkali metals, sodium and potassium may be mentioned.
[0121] Examples of the phosphoric acid ester include at least one phosphoric acid ester compound selected from the group consisting of formula (4) to formula (6).
[0122] In formulae (4) to (6), X1, X2, and X3 each represent an alkylene group having 2 to 20 carbon atoms, f, h, and j each represent an integer from 1 to 100, e, g, and i each represent an integer from 1 to 3, and Y1, Y2, and Y3 each represent a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, or a (meth)acryloyl group.
[0123] As the phosphate ester, polyoxyethylene alkyl ether phosphate ester can be preferably used. For example, the phosphate ester can be a phosphate ester in which the terminal alkyl group (Y1) in the above formula (4) represents an alkyl group having 6 to 10 or 12 to 15 carbon atoms. For example, products such as those manufactured by Toho Chemical Industry Co., Ltd. under the trade names of Fosfarnol RA-600 and RS-610 can be used.
[0124] As the surfactant, an anionic surfactant, a cationic surfactant, an amphoteric surfactant, and a nonionic surfactant can be used.
[0125] Examples of the anionic surfactant used in the present invention include sodium and potassium salts of fatty acids, alkylbenzene sulfonates, higher alcohol sulfate ester salts, polyoxyethylene alkyl ether sulfates, α-sulfofatty acid esters, α-olefin sulfonates, monoalkyl phosphate ester salts, and alkane sulfonates.
[0126] For example, examples of the alkylbenzene sulfonate include sodium salts, potassium salts, and lithium salts, and examples include sodium C10-C16 alkylbenzene sulfonate, C10-C16 alkylbenzene sulfonic acid, and sodium alkylnaphthalene sulfonate.
[0127] Examples of the higher alcohol sulfuric acid ester salt include sodium dodecyl sulfate (sodium lauryl sulfate) having 12 carbon atoms, triethanolamine lauryl sulfate, and triethanolammonium lauryl sulfate.
[0128] Examples of the polyoxyethylene alkyl ether sulfates include sodium polyoxyethylene styrenated phenyl ether sulfate, ammonium polyoxyethylene styrenated phenyl ether sulfate, sodium polyoxyethylene decyl ether sulfate, ammonium polyoxyethylene decyl ether sulfate, sodium polyoxyethylene lauryl ether sulfate, ammonium polyoxyethylene lauryl ether sulfate, sodium polyoxyethylene tridecyl ether sulfate, and sodium polyoxyethylene oleyl cetyl ether sulfate.
[0129] Examples of the α-olefin sulfonate include sodium α-olefin sulfonate and the like.
[0130] Examples of the alkanesulfonate include sodium 2-ethylhexyl sulfate and the like.
[0131] Examples of the cationic surfactant used in the present invention include alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, and amine salt-based agents.
[0132] The alkyltrimethylammonium salt is a quaternary ammonium salt having a chloride ion or a bromide ion as a counter ion, and examples thereof include dodecyltrimethylammonium chloride, cetyltrimethylammonium chloride, coconut oil alkyltrimethylammonium chloride, and alkyl (C16-18)trimethylammonium chloride.
[0133] The dialkyldimethylammonium salt has two main chains that become lipophilic and two methyl groups. For example, di(hydrogenated tallow)dimethylammonium chloride can be mentioned. For example, didecyldimethylammonium chloride, dicocoalkyldimethylammonium chloride, dihydrogenated tallowalkyldimethylammonium chloride, dialkyl(C14-18)dimethylammonium chloride can be mentioned.
[0134] The alkyl dimethyl benzyl ammonium salt is a quaternary ammonium salt having one lipophilic main chain, two methyl groups and one benzyl group, and an example thereof is benzalkonium chloride. For example, an example thereof is alkyl (C8-18) dimethyl benzyl ammonium chloride.
[0135] The amine salt-based agent is a substance obtained by replacing the hydrogen atom of ammonia with one or more hydrocarbon groups, and an example thereof is N-methylbishydroxyethylamine fatty acid ester hydrochloride.
[0136] Examples of the amphoteric surfactant used in the present invention include N-alkyl-β-alanine type alkylamino fatty acid salts, alkyl carboxy betaine type alkyl betaines, and N,N-dimethyl dodecylamine oxide type alkyl amine oxides. Examples thereof include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazoline Betaine, Lauryl Dimethylamine Oxide.
[0137] Examples of the nonionic surfactant used in the present invention include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, alkyl glucosides, polyoxyethylene fatty acid esters, sucrose fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and fatty acid alkanolamides. For example, examples of the polyoxyethylene alkyl ethers include polyoxyethylene dodecyl ether (polyoxyethylene lauryl ether), polyoxyethylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene myristyl ether, polyoxyethylene cetyl ether, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene behenyl ether, polyoxyethylene-2-ethylhexyl ether, and polyoxyethylene isodecyl ether.
[0138] Examples of the polyoxyethylene alkylphenol ethers include polyoxyethylene styrenated phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene distyrenated phenyl ether, and polyoxyethylene tribenzylphenyl ether.
[0139] Examples of the alkyl glucoside include decyl glucoside and lauryl glucoside.
[0140] Examples of the polyoxyethylene fatty acid ester include polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, polyethylene glycol distearate, polyethylene glycol dioleate, and polypropylene glycol dioleate.
[0141] Examples of the sorbitan fatty acid esters include sorbitan monocaprylate, sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan monosesquioleate, and ethylene oxide adducts thereof.
[0142] Examples of the polyoxyethylene sorbitan fatty acid esters include polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan triisostearate.
[0143] Examples of fatty acid alkanolamides include coconut fatty acid diethanolamide, tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.
[0144] Furthermore, examples of the surfactant include polyoxyalkyl ethers or polyoxyalkyl glycols such as polyoxyethylene polyoxypropylene glycol and polyoxyethylene fatty acid esters, polyoxyethylene hydrogenated castor oil ether, sorbitan fatty acid ester alkyl ethers, alkyl polyglucosides, sorbitan monooleate, and sucrose fatty acid esters.
[0145] The method for producing the above-mentioned composition of the present invention comprises the following steps (i) and (ii),
[0146] Step (i): a step of mixing photoactive metal oxide particles (A), a dispersant (B), and an organic solvent (C) other than a volatile aldehyde compound,
[0147] Step (ii): a step (ii) of removing the alcohol having 1 to 2 carbon atoms in the liquid obtained in step (i) until the alcohol having 1 to 2 carbon atoms is contained in the entire solvent in a proportion of 200 ppm or less.
[0148] The alcohol having 1 to 2 carbon atoms can be removed by, for example, evaporation or ultrafiltration.
[0149] The composition obtained by the above production method may have a solid content of 0.1 to 70% by mass, with the photoactive metal oxide particles (A) accounting for 80 to 99% by mass and the dispersant (B) accounting for 1 to 20% by mass in the total solid content.
[0150] Here, the solid content refers to a component obtained by removing the solvent component from the composition, and the solid content concentration refers to the concentration of the solid content in the composition.
[0151] In addition, at 0.4mW / cm 2 When 15 g of the composition is irradiated with ultraviolet light having a wavelength of 365 nm at an intensity of 1000 nm for 4 hours, the proportion of volatile aldehyde compounds generated in the composition is 2 ppm or less. The volatile aldehyde compounds are preferably 0.001 to 2 ppm, or 0.01 to 1 ppm.
[0152] If the composition is stored in a brown container, the photocatalytic effect can be reduced. However, conventional compositions have problems such as generation of volatile aldehyde compounds due to photocatalytic effect when stored in a transparent container, during the process of transferring the composition from the container to the device for use, and when applied to a substrate.
[0153] However, the composition of the present invention can suppress the generation of volatile aldehydes by setting the ratio of the alcohol having 1 to 2 carbon atoms contained in the composition to 200 ppm or less. Furthermore, it is known that a dispersant (B) is required to disperse the photoactive metal oxide particles (A) in the organic solvent (C) having the above characteristics.
[0154] The composition of the present invention can be further mixed with a thermosetting or photocurable resin to produce a varnish.
[0155] Furthermore, a varnish containing a curing agent such as an amine curing agent, an acid anhydride curing agent, or an acid generator curing agent (thermal acid generator or photoacid generator) can be made into a cured product. The varnish containing the present composition, resin and curing agent can be applied or filled on a substrate, and a cured product can be formed by heating, light irradiation, or a combination thereof. As the curable resin, a resin having a functional group such as an epoxy group or a (meth)acryloyl group can be cited.
[0156] In the case of a thermosetting varnish, the thermosetting agent may be contained in a ratio of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents, to the epoxy group or (meth)acryloyl group or other functional groups of the resin. The equivalent of the thermosetting agent to the curable resin is represented by the equivalent ratio of the thermosetting agent to the functional group.
[0157] Examples of the thermosetting agent include phenolic resins, amine-based curing agents, polyamide resins, imidazoles, polythiol, acid anhydrides, thermal acid generators, etc. Acid anhydride-based curing agents and amine-based curing agents are particularly preferred.
[0158] These thermosetting agents can be used even if they are solid by being dissolved in a solvent. However, the density of the cured product decreases due to evaporation of the solvent, and the strength and water resistance of the cured product decrease due to the formation of pores. Therefore, the curing agent itself is preferably liquid at room temperature and pressure.
[0159] Examples of the phenol resin include phenol novolac resin and cresol novolac resin.
[0160] Examples of the amine curing agent include piperidine, N,N-dimethylpiperazine, triethylenediamine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthenediamine, isophoronediamine, diaminodicyclohexylmethane, 1,3-diaminomethylcyclohexane, xylylenediamine, m-phenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and diethyltoluenediamine. Among them, preferably used are liquid diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthene diamine, isophoronediamine, diaminodicyclohexylmethane, 3,3′-diethyl-4,4′-diaminodiphenylmethane, diethyltoluenediamine and the like.
[0161] The polyamide resin is produced by condensation of a dimer acid and a polyamine, and is a polyamide amine having a primary amine and a secondary amine in the molecule.
[0162] Examples of the imidazoles include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, Trimellitate, epoxy imidazole adduct, etc.
[0163] Examples of the polythiol include those having a thiol group at the end of a polypropylene glycol chain and those having a thiol group at the end of a polyethylene glycol chain, and liquid ones are preferred.
[0164] As the acid anhydride curing agent, an anhydride of a compound having a plurality of carboxyl groups in one molecule is preferred. As these acid anhydride curing agents, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, ethylene glycol ditrimellitate, glycerol trimellitate, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, succinic anhydride, methylcyclohexene dicarboxylic anhydride, chlorendic anhydride, etc. can be cited.
[0165] Examples of the thermal acid generator include sulfonium salts, Onium salts are used, but sulfonium salts are preferably used. The following compounds can be exemplified.
[0166]
[0167] In the formula, R represents an alkyl group having 1 to 12 carbon atoms or an aryl group having 6 to 20 carbon atoms, and an alkyl group having 1 to 12 carbon atoms is particularly preferred.
[0168] Among them, methyltetrahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic anhydride (methylnadic anhydride, methylnadic anhydride), hydrogenated methylnadic anhydride, methylbutenyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, methylhexahydrophthalic anhydride, and a mixture of methylhexahydrophthalic anhydride and hexahydrophthalic anhydride, which are liquid at room temperature and pressure, are preferred. The viscosity of these liquid anhydrides is about 10 mPas to 1000 mPas as measured at 25°C.
[0169] In addition, when obtaining the above-mentioned cured product, a curing aid may be used in combination as appropriate. Examples of the curing aid include organic phosphorus compounds such as triphenylphosphine and tributylphosphine, ethyltriphenylphosphine bromide, Methyltriphenyl Diethyl phosphate and other quaternary Salts, 1,8-diazabicyclo(5,4,0)undec-7-ene, salts of 1,8-diazabicyclo(5,4,0)undec-7-ene and octanoic acid, zinc octanoate, tetrabutylammonium bromide and other quaternary ammonium salts. These curing aids can be contained in a ratio of 0.001 to 0.1 parts by mass based on 1 part by mass of the curing agent.
[0170] The composition, resin, curing agent and, if necessary, curing aid are mixed to obtain a thermosetting varnish. These can be mixed in a reaction vessel using a stirring blade or a kneader.
[0171] The mixing is performed by a heating mixing method at a temperature of 60°C to 100°C for 0.5 to 1 hour.
[0172] The obtained curable resin varnish (thermosetting composition) is a thermosetting coating composition having an appropriate viscosity for use as, for example, a liquid sealing material. The liquid thermosetting varnish can be modulated to any viscosity, and in order to be used as a transparent sealing material such as an LED by a casting method, a pouring method, a dispenser method, a printing method, etc., a partial seal can be performed at any position thereof. The liquid thermosetting composition is directly mounted on an LED, etc. in a liquid state by the above method, and then dried and cured to obtain an epoxy resin cured body.
[0173] The thermosetting varnish (thermosetting coating composition) is applied to a substrate and heated at a temperature of 80 to 200° C. to obtain a cured product.
[0174] In the case of a photocurable varnish, a photocuring agent (photoacid generator) may be contained in a ratio of 0.5 to 20% by mass, preferably 0.8 to 10% by mass, based on the functional groups such as epoxy groups and (meth)acryloyl groups in the resin.
[0175] The photoacid generator is not particularly limited as long as it generates an acid directly or indirectly by light irradiation.
[0176] Specific examples of the photoacid generator include triazine compounds, acetophenone derivative compounds, disulfone compounds, diazomethane compounds, sulfonic acid derivative compounds, iodine compounds, Salt, sulfonium salt, Salt, selenium salt, etc. Salts, metallocene coordination compounds, iron arene coordination compounds, etc.
[0177] As the above-mentioned photoacid generator, In salt, as iodine Salts such as diphenyl iodide Chloride, diphenyl iodide Trifluoromethanesulfonate, diphenyl iodide Methanesulfonate, diphenyl iodide Tosylate, diphenyl iodide Bromide, diphenyl iodide Tetrafluoroborate, diphenyl iodide Hexafluoroantimonate, diphenyl iodide Hexafluoroarsenate, bis(p-tert-butylphenyl)iodide Hexafluorophosphate, bis(p-tert-butylphenyl)iodide Methanesulfonate, bis(p-tert-butylphenyl)iodide Toluenesulfonate, bis(p-tert-butylphenyl)iodide Trifluoromethanesulfonate, bis(p-tert-butylphenyl)iodide Tetrafluoroborate, bis(p-tert-butylphenyl)iodide Chloride, bis(p-chlorophenyl)iodide Chloride, bis(p-chlorophenyl)iodide Tetrafluoroborate, further bis(4-tert-butylphenyl)iodide Hexafluorophosphate and other bis(alkylphenyl)iodides Salts, alkoxycarbonylalkoxy-trialkylaryl iodides Salts (e.g., 4-[(1-ethoxycarbonyl-ethoxy)phenyl]-(2,4,6-trimethylphenyl)-iodine Hexafluorophosphate, etc.), bis(alkoxyaryl)iodide Salts (e.g., (4-methoxyphenyl)phenyl iodide Hexafluoroantimonate, etc. Bis(alkoxyphenyl)iodide Salt).
[0178] Examples of the sulfonium salt include triphenylsulfonium chloride, triphenylsulfonium bromide, tri(p-methoxyphenyl)sulfonium tetrafluoroborate, tri(p-methoxyphenyl)sulfonium hexafluorophosphonate, tri(p-ethoxyphenyl)sulfonium tetrafluoroborate, triphenylsulfonium trifluoromethanesulfonate, triphenylsulfonium hexafluoroantimonate, and triphenylsulfonium hexafluorophosphate; and sulfonium salts such as (4-phenylthiophenyl)diphenylsulfonium hexafluoroantimonate, (4-phenylthiophenyl)diphenylsulfonium hexafluorophosphate, bis[4-(diphenylsulfonyl)phenyl]sulfide-bis-hexafluoroantimonate, bis[4-(diphenylsulfonyl)phenyl]sulfide-bis-hexafluorophosphate, and (4-methoxyphenyl)diphenylsulfonium hexafluoroantimonate.
[0179] As Salts such as triphenyl Chloride, triphenyl Bromide, tris(p-methoxyphenyl) Tetrafluoroborate, tris(p-methoxyphenyl) Hexafluorophosphonate, tris(p-ethoxyphenyl) Tetrafluoroborate, 4-chlorobenzenediazonium Hexafluorophosphate, benzyltriphenylphosphine Hexafluoroantimonate, etc. Salt.
[0180] Examples include selenium salts such as triphenylselenium hexafluorophosphate and metallocene complexes such as (η5 or η6-isopropylbenzene)(η5-cyclopentadienyl)iron(II) hexafluorophosphate.
[0181] Furthermore, as the photoacid generator, the following compounds can also be used.
[0182]
[0183]
[0184]
[0185]
[0186]
[0187]
[0188]
[0189] As the photoacid generator, sulfonium salt compounds, iodine Salt compounds. Examples of these anionic species include CF3SO3 - 、C4F9SO3 - 、C8F 17 SO3 - , camphorsulfonic acid anion, toluenesulfonic acid anion, BF4 - PF6 - 、AsF6 - and SbF6 - etc. Anionic species showing strong acidity such as phosphorus hexafluoride and antimony hexafluoride are particularly preferred.
[0190] The composition and varnish of the present invention may contain conventional additives as required. Such additives include, for example, pigments, colorants, thickeners, sensitizers, defoamers, leveling agents, coating improvers, lubricants, stabilizers (antioxidants, heat stabilizers, light stabilizers, etc.), plasticizers, dissolution promoters, fillers, antistatic agents, etc. These additives may be used alone or in combination of two or more.
[0191] Examples of the coating method for the composition and varnish of the present invention include flow coating, spin coating, spray coating, screen printing, casting, rod coating, curtain coating, roll coating, gravure coating, dipping, and slit coating.
[0192] In the present invention, the photocoating composition can be coated on a substrate and cured by light irradiation. Alternatively, heating can be performed before or after light irradiation.
[0193] The thickness of the coating film can be selected from the range of about 0.01μm to 10mm depending on the use of the cured product. For example, when used for photoresists, it can be about 0.05~10μm (especially 0.1~5μm), when used for printed wiring substrates, it can be about 5μm~5mm (especially 100μm~1mm), and when used for optical films, it can be about 0.1~100μm (especially 0.3~50μm).
[0194] When a photoacid generator is used, the light for irradiation or exposure may be, for example, gamma rays, X-rays, ultraviolet rays, visible rays, etc., and is usually visible light or ultraviolet rays, especially ultraviolet rays. The wavelength of the light is, for example, 150 to 800 nm, preferably 150 to 600 nm, more preferably 200 to 400 nm, especially about 300 to 400 nm. The amount of irradiation light varies depending on the thickness of the coating film, but may be, for example, 2 to 20,000 mJ / cm 2 , preferably 5 to 5000 mJ / cm 2 As a light source, it can be selected according to the type of light for exposure. For example, in the case of ultraviolet rays, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a deuterium lamp, a halogen lamp, a laser (helium-cadmium laser, excimer laser, etc.) can be used. By such light irradiation, the curing reaction of the above-mentioned composition proceeds.
[0195] When a thermal acid generator is used, the coating film is heated as required after light irradiation using a photoacid generator, for example, at 60 to 250° C., preferably at about 100 to 200° C. The heating time can be selected from a range of 3 seconds or more (for example, about 3 seconds to 5 hours), for example, 5 seconds to 2 hours, preferably about 20 seconds to 30 minutes, and usually about 1 minute to 3 hours (for example, 5 minutes to 2.5 hours).
[0196] Furthermore, in the case of forming a pattern or an image (for example, in the case of manufacturing a printed wiring board, etc.), the coating film formed on the substrate can be subjected to pattern exposure, and the pattern exposure can be performed by scanning with a laser or by irradiating light through a photomask. The pattern or image can be formed by developing (or dissolving) the non-irradiated area (unexposed portion) generated by such pattern exposure with a developer.
[0197] As the developer, an aqueous alkaline solution or an organic solvent can be used.
[0198] Examples of the aqueous alkali solution include aqueous solutions of alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, potassium carbonate, and sodium carbonate; aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine.
[0199] The alkaline developer is generally an aqueous solution of 10% by mass or less, preferably 0.1 to 3.0% by mass. The developer may further contain alcohols and surfactants, preferably 0.05 to 10 parts by mass, respectively, based on 100 parts by mass of the developer.
[0200] Among them, a 0.1 to 2.38 mass % aqueous solution of tetramethylammonium hydroxide can be used.
[0201] In addition, as the organic solvent of the developer, a general organic solvent can be used, for example, acetone, acetonitrile, toluene, dimethylformamide, methanol, ethanol, isopropanol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol butyl ether acetate, ethyl lactate, cyclohexanone, etc., and they can be used in the form of one or a mixture of two or more thereof. In particular, propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, etc. can be preferably used.
[0202] In the present invention, a close adhesion promoter may be added to the varnish for the purpose of improving the close adhesion to the substrate after development. Examples of these close adhesion promoters include chlorosilanes such as trimethylchlorosilane, dimethylvinylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane; alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylvinylethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane; hexamethyldisilazane; N,N'-bis(trimethylsilyl)urea; dimethyltrimethylsilane; Silanes such as silylamine, trimethylsilyl imidazole, vinyl trichlorosilane, γ-chloropropyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-glycidoxypropyl trimethoxysilane, γ-(N-piperidyl)propyl trimethoxysilane, benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-mercaptobenzo Heterocyclic compounds such as azoles, urea, thiouracil, mercaptoimidazole, and mercaptopyrimidine, ureas such as 1,1-dimethylurea and 1,3-dimethylurea, or thiourea compounds. One or more of the above-mentioned adhesion promoters can be used in combination. The amount of these adhesion promoters added is usually 18% by mass or less, preferably 0.0008 to 9% by mass, and more preferably 0.04 to 9% by mass in the solid content.
[0203] The composition and varnish of the present invention may contain a sensitizer. Examples of usable sensitizers include anthracene, phenothiazine, perylene, thioxanthone, benzophenone, and thioxanthone. Further, examples of sensitizing pigments include thiopyran Salt-based pigments, merocyanine-based pigments, quinoline-based pigments, styrylquinoline-based pigments, ketocoumarin-based pigments, thioxanthene-based pigments, xanthene-based pigments, oxonol-based pigments, cyanine-based pigments, rhodamine-based pigments, pyranose Salt-based pigments, etc. Particularly preferred are anthracene-based sensitizers, which can dramatically improve sensitivity by using them in combination with a cationic curing catalyst (radiation-sensitive cationic polymerization initiator), and also have a free radical polymerization initiation function. For a hybrid type in which the cationic curing system of the present invention is used in combination with a free radical curing system, the catalyst species can be simplified. As specific anthracene compounds, dibutoxyanthracene, dipropoxyanthraquinone, etc. are effective. The sensitizer is added in an amount of 0.01 to 20% by mass, preferably 0.01 to 10% by mass, in the solid component.
[0204] The varnish of the present invention can be photocured or thermally cured using a photoacid generator or a thermal acid generator. Since a photoacid generator or a thermal acid generator is used, a curing agent (such as amine or anhydride) commonly used for epoxy is not used or even if it is used, the content thereof is extremely small, so that the storage stability of the varnish is improved.
[0205] The varnish can be applied to photocationically polymerizable resins. It has a high curing speed compared to existing liquid epoxy compounds (e.g., alicyclic epoxy compounds having an epoxycyclohexyl ring). Due to the high curing speed, the amount of acid generator added can be reduced and a weak acid generator can be used. The reduction of the acid generator is important for preventing metal corrosion due to residual acid active species after UV irradiation. Due to the high curing speed, thick film curing can be performed.
[0206] Curing using UV radiation can be applied to heat-sensitive materials (mechanical materials).
[0207] The thermosetting material and photocuring material using the varnish containing the epoxy compound of the present invention have the characteristics of rapid curing, transparency, small curing shrinkage, etc., and can be used for covering and bonding electronic parts, optical parts, and precision mechanism parts. For example, it can be used for bonding mobile phones, camera lenses, light-emitting diodes (LEDs), semiconductor lasers (LDs) and other optical elements, liquid crystal panels, biochips, camera lenses, prisms and other parts, magnetic parts of hard disks of personal computers, etc., pickup devices of CD and DVD players (parts that introduce light information reflected from the disk), speaker cones and coils, motor magnets, circuit boards, electronic parts, and parts inside engines of automobiles, etc.
[0208] As a hard coating material for surface protection of automobile bodies, lamps, electrical products, building materials, plastics, etc., it can be applied to, for example, automobile and bicycle bodies, headlight lenses, mirrors, plastic lenses of glasses, mobile phones, game consoles, optical films, ID cards, etc.
[0209] Examples of ink materials for printing on metals such as aluminum, plastics, and the like include printing inks for cards such as credit cards and membership cards, electronic products, switches and keyboards of OA equipment, and inks for inkjet printers for CDs and DVDs.
[0210] Examples include applications to technology for curing resins to create complex three-dimensional objects in combination with 3D CAD, applications to optical modeling such as modeling of industrial products, and applications to coating, bonding, optical waveguides, thick film resists, and the like for optical fibers.
[0211] In addition, the composition for forming a cured body containing the composition of the present invention can be suitably used as an insulating resin for electronic materials such as semiconductor sealing materials, adhesives for electronic materials, printed wiring board materials, interlayer insulating film materials, and sealing materials for power modules, and an insulating resin used in high-voltage equipment such as generator coils, transformer coils, and gas-insulated switchgear.
[0212] Furthermore, although examples of the composition of the present invention are given, the present invention is not limited to these.
[0213] For example, in the present invention, a sol containing photoactive titanium oxide particles having a molar ratio of quaternary ammonium ions to titanium atoms of 0.1 to 1.5 and a molar ratio of amino acids to titanium atoms of 0.1 to 1.5, and having an average particle size of 5 to 500 nm can be used. The average particle size can be determined by dynamic light scattering.
[0214] The coexistence of quaternary ammonium ions and amino acids allows titanium oxide particles to exist stably, and is particularly effective in a sol containing titanium oxide particles having an average particle size exceeding 100 nm as obtained by dynamic light scattering, such as 100 to 500 nm, 110 to 300 nm, or 110 to 250 nm.
[0215] Examples of the raw material of titanium oxide contained in the sol include titanium oxide particles obtained by a pulverization method, titanium oxide particles obtained by hydrolysis of titanium sulfate or titanyl sulfate, titanium oxide particles obtained from a polymer of titanium hydroxide, and titanium oxide particles obtained by hydrolysis and condensation of titanium alkoxide.
[0216] The sol containing titanium oxide particles can be a sol containing core-shell metal oxide particles with the titanium oxide particles as cores, whose surfaces are coated with metal oxide particles containing silicon dioxide, and titanium oxide particles containing 50 mol% or more and 99 mol% or less of titanium oxide in all metal oxides. The photoactivity of titanium oxide can be suppressed by coating the surface of the titanium oxide particles that become the core. As the object, titanium oxide particles containing 50 mol% or more and 99 mol% or less of titanium oxide in all metal oxides are suitable. The metal oxide particles used for coating can be metal oxide particles or composite metal oxide particles selected from at least one of silicon dioxide, tin oxide, antimony oxide, tungsten oxide, aluminum oxide, and zirconium oxide. The proportion of coating can be the above proportion.
[0217] As the quaternary ammonium ion, tetramethylammonium hydroxide or tetraethylammonium hydroxide-based substances can be preferably used. The use of a water-soluble alkaline substance can contribute to the promotion of the hydrolysis of the raw material and the dispersibility of the obtained titanium oxide particles.
[0218] As the amino acid, glycine, alanine, valine, norvaline, leucine, norleucine, isoleucine, phenylalanine, tyrosine, diiodotyrosine, methyltyrosine, threonine, serine, proline, hydroxyproline, tryptophan, thyroxine, methionine, cystine, cysteine, α-aminobutyric acid, aspartic acid, glutamic acid, asparagine, glutamine, lysine, hydroxylysine, arginine, or histidine can be used, and glycine is particularly useful. These amino acids are water-soluble and coordinate with quaternary ammonium ions to contribute to the dispersion stability of the particles during the formation of titanium oxide particles. Therefore, the particle growth of titanium oxide particles is promoted, titanium oxide particles with large particle size are formed, and a stably dispersed titanium oxide sol is formed.
[0219] The sol containing titanium oxide can be produced by subjecting an aqueous medium containing a titanium compound, quaternary ammonium hydroxide, and an amino acid to a hydrothermal reaction at 100 to 300°C.
[0220] The hydrothermal reaction may be carried out by heating the reaction mixture for about 0.1 to 10 hours using an autoclave apparatus, or by pre-stirring the reaction mixture at a temperature of about 60 to 100° C. before the hydrothermal treatment.
[0221] Example
[0222] The physical properties of the composition were determined by the following measurement methods.
[0223] [Viscosity] The viscosity was determined using an Ostwald viscometer (25° C.).
[0224] [Water content] was determined using Karl Fischer titration.
[0225] [Average particle size obtained by dynamic light scattering (dynamic light scattering particle size)] The composition was diluted with a dispersion solvent and measured using parameters of the solvent using a dynamic light scattering measuring apparatus: Zeta-Sizer manufactured by Malvern Instruments Ltd.
[0226] The amounts of methanol and formaldehyde in the compositions obtained in Examples and Comparative Examples were measured and evaluated by the following measurement methods.
[0227] (1) Methanol amount
[0228] The amount of methanol in the composition was determined using a gas chromatograph (GC-2014 manufactured by Shimadzu Corporation) under the following conditions.
[0229] Column: 3mm×1m glass column
[0230] Filler: ポーラパックQ
[0231] Column temperature: 130-230°C (temperature increase 8°C / min)
[0232] Carrier: N2 40mL / min
[0233] Detector: FID
[0234] Injection volume: 1 μL
[0235] Internal standard: acetonitrile
[0236] (2) Formaldehyde content
[0237] After the particles and the solvent were separated by centrifugal ultrafiltration, the solvent was diluted 10 times with methanol, and 0.02 mL of 20% phosphoric acid aqueous solution and 0.5 mL of 1000 ppm DNPH acetonitrile solution were added to 1 mL of the diluent. The resulting solution was heated with an aluminum block heater at 60°C for 60 minutes. It was quantified using a high performance liquid chromatography (ACQUITY UltraPerformance LC manufactured by Waters) under the following conditions.
[0238] Column: ACQUITY UPLC BEH c18 1.7um 2.1×100mm
[0239] Flow rate: 0.3mL / min
[0240] Mobile phase: acetonitrile / water = 55 / 45
[0241] Injection volume: 3 μL
[0242] Column temperature: 40°C
[0243] Detector: PDA (360nm)
[0244] The calibration curve used a mixed standard stock solution of aldehydes-2,4-DNPH (for HPLC) manufactured by Kanto Chemical Co., Ltd. As a calibration for the DNPH reaction rate, a sample pretreated with the above-mentioned steps and diluted to 0.1 ppm with the formaldehyde standard solution was measured.
[0245] (3) Light resistance test
[0246] 15 g of the composition was added to a screw bottle and irradiated with a UV lamp (Handy UVLamp SLUV-6 manufactured by Aswan) for 4 hours. The formaldehyde content in the liquid was analyzed by the above steps. The UV wavelength was 365 nm and the UV intensity was 0.4 mW / cm 2 .
[0247] (Reference Example 1: Preparation of Titanium Oxide-Tin Oxide Composite Oxide Colloidal Particles (A1) as Cores)
[0248] 319.5 g of 25% by mass tetramethylammonium hydroxide aqueous solution was dissolved in 947.1 g of pure water, and then 14.8 g of metastannic acid (12.5 g in terms of SnO2), 236.6 g of titanium tetraisopropoxide (66.6 g in terms of TiO2), and 82.0 g of oxalic acid dihydrate (58.5 g in terms of oxalic acid) were added under stirring. The mixed solution was kept at 80°C for 2 hours, and the pressure was further reduced to 580 Torr and kept for 2 hours to prepare a mixed solution. The mixed solution was placed in a glass-lined autoclave container, hydrothermally treated at 140°C for 5 hours, cooled to room temperature, and then taken out. The obtained sol was an acidic water-dispersed sol of titanium oxide-tin oxide composite oxide colloidal particles (A1), with a pH of 3.9, a total metal oxide concentration (TiO2, and SnO2) of 5.0% by mass, and an average particle size (dynamic light scattering method particle size) of 16 nm obtained by dynamic light scattering. The obtained sol was dried at 110° C., and the powder obtained was subjected to X-ray diffraction analysis, which confirmed that the powder was a rutile crystal.
[0249] (Reference Example 2: Preparation of Silica-Tin Oxide Composite Oxide Colloidal Particles (B1) as Coating)
[0250] 77.2 g of JIS No. 3 sodium silicate (containing 29.8% by mass in terms of SiO2) was dissolved in 668.8 g of pure water, and then 20.9 g of sodium stannate NaSnO3·H2O (containing 55.1% by mass in terms of SnO2) was dissolved. The obtained aqueous solution was passed through a column filled with a hydrogen-type cation exchange resin (Anvalite (registered trademark) IR-120B). Then, 7.2 g of diisopropylamine was added to the obtained water-dispersed sol. The obtained sol was an alkaline water-dispersed sol of silica-tin oxide composite oxide colloidal particles (B1) with a pH of 8.0 and a total metal oxide concentration (SiO2 and SnO2) of 1.7% by mass. The primary particle size was 1 to 4 nm as observed by a transmission electron microscope.
[0251] (Production Example 1: Preparation of Titanium Oxide-Tin Oxide-Zirconium Oxide Composite Oxide Colloidal Particles (C1) Modified with Silicon Dioxide-Tin Oxide Composite Oxide)
[0252] 82.7 g of zirconium oxychloride (containing 21.2% by mass as calculated as ZrO2) was diluted with 501.1 g of pure water to prepare 583.8 g of zirconium oxychloride aqueous solution (containing 3.0% by mass as calculated as ZrO2), and 1516.2 g of the water-dispersed sol of the titanium oxide-tin oxide composite oxide colloidal particles (A1) prepared in Reference Example 1 was added under stirring. The mixture was then heated to 95° C. for hydrolysis, thereby obtaining a water-dispersed sol of titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles having a thin film layer of zirconium oxide formed on the surface. 2041.2 g of the obtained water-dispersed sol was added to 1763.3 g of the water-dispersed sol of the alkaline silica-tin oxide composite oxide colloidal particles (B1) prepared in Reference Example 2 under stirring, and the mixture was passed through a column filled with 500 ml of an anion exchange resin (Anvaliate (registered trademark) IRA-410, manufactured by Organo Co., Ltd.). The water-dispersed sol after the passage was heated at 95° C. for 3 hours and then concentrated by ultrafiltration to obtain a water-dispersed sol of titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with silica-tin oxide composite oxide. The water-dispersed sol had a pH of 5.2, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 5.0 mPa·s, and an average particle size (dynamic light scattering particle size) of 20 nm as determined by dynamic light scattering (DLS).
[0253] (Reference Example 3: Preparation of Zirconium Oxide-Tin Oxide Composite Oxide Colloidal Particles (A2) as Cores)
[0254] 293.7 g of tetramethylammonium bicarbonate (containing 42.4% by mass as tetramethylammonium hydroxide) aqueous solution was diluted with 111.5 g of pure water, and 168.4 g of zirconium carbonate powder (containing 40.1% by mass as ZrO2) was slowly added while stirring the aqueous solution. After the addition was completed, the mixture was heated to 85°C, 9.6 g of metastannic acid (containing 86.0% by mass as SnO2) was slowly added, and the mixture was heated and aged at 105°C for 5 hours, and further hydrothermally treated at 145°C for 5 hours. The sol was then washed and concentrated by adding pure water using an ultrafiltration device. The obtained sol was an alkaline water-dispersed sol of zirconium oxide-tin oxide composite oxide colloidal particles (A2), pH 9.4, total metal oxide concentration (total of ZrO2 and SnO2) 5.0% by mass, and the average particle size obtained by dynamic light scattering (dynamic light scattering particle size) was 15 nm.
[0255] (Production Example 2: Preparation of zirconium oxide-tin oxide composite oxide colloidal particles (C2) modified with silicon dioxide-tin oxide composite oxide)
[0256] 830.4 g of the aqueous dispersion sol of the alkaline silica-tin oxide composite oxide colloidal particles (B1) prepared in Reference Example 2 was added to 1411.7 g of the aqueous dispersion sol of the alkaline zirconium oxide-tin oxide composite oxide colloidal particles (A2) obtained in Reference Example 3 under stirring. The mixture was then heated to 95° C. and maintained for 2 hours, and then passed through a column filled with a hydrogen-type cation exchange resin (Anvaliate (registered trademark) IR-120B). The sol after passing through the column was concentrated by ultrafiltration to obtain an aqueous dispersion sol of zirconium oxide-tin oxide composite oxide colloidal particles (C2) modified with silica-tin oxide composite oxide. The aqueous dispersion sol had a pH of 5.0, a total metal oxide (ZrO2, SnO2, and SiO2) concentration of 30% by mass, a viscosity of 5.3 mPa·s, and an average particle size (dynamic light scattering particle size) of 20 nm as determined by a dynamic light scattering method (DLS).
[0257] (Reference Example 4: Preparation of Tin Oxide Colloidal Particles (A3) as Cores)
[0258] 64.0 g of oxalic acid dihydrate (45.7 g in terms of oxalic acid) was dissolved in 723.3 g of pure water, and after heating to 70°C while stirring, 290.3 g of 35% hydrogen peroxide and 128.1 g of metal tin powder (99.7% in terms of SnO2) were added. The addition of hydrogen peroxide and metal tin was performed alternately 10 times. First, 29.0 g of 35% hydrogen peroxide was added, followed by 12.8 g of metal tin. This operation was repeated (10 to 15 minutes) while waiting for the reaction to end. The time required for the addition was 2 hours, and after the addition was completed, the reaction was completed by heating for 2 hours while keeping the liquid temperature at 90°C. Next, 394.5 g of 35% hydrogen peroxide was added and kept at 90°C for 5 hours. Next, 5.1 g of isopropylamine was added, and after being kept at 50° C. for 3 hours, the mixture was passed through a column filled with 500 ml of anion exchange resin (Anvaliate (registered trademark) IRA-410). The obtained sol was a water-dispersed sol of alkaline tin oxide composite oxide colloidal particles (A3), pH 11.0, SnO2 concentration 4.0% by mass, and the average particle size obtained by dynamic light scattering (dynamic light scattering method particle size) was 20 nm.
[0259] (Production Example 3: Preparation of Tin Oxide Colloidal Particles (C3) Modified with Silica-Tin Oxide Composite Oxide)
[0260] To 1458.8 g of the water-dispersed sol of the tin oxide colloidal particles (A3) obtained in Reference Example 4, 514.9 g of the water-dispersed sol of the alkaline silica-tin oxide composite oxide colloidal particles (B1) prepared in Reference Example 2 was added under stirring. Then, the mixture was heated to 95° C. and maintained for 2 hours, and then passed through a column filled with a hydrogen-type cation exchange resin (Anvaliate (registered trademark) IR-120B). The sol after passing through the column was concentrated by ultrafiltration to obtain a water-dispersed sol of the tin oxide colloidal particles (C3) modified with the silica-tin oxide composite oxide. The water-dispersed sol had a total metal oxide (SnO2 and SiO2) concentration of 30.5% by mass, a viscosity of 4.8 mPa·s, and an average particle size (dynamic light scattering particle size) of 18 nm as obtained by dynamic light scattering (DLS).
[0261] (Reference Example 5: Preparation of Titanium Oxide Colloidal Particles (A4) as Cores)
[0262] 1431.0 g of pure water was added to a 5-liter container, and 315.0 g of a 35% by mass aqueous solution of tetraethylammonium hydroxide, 39.6 g of glycine, and 213.2 g of titanium tetraisopropoxide (59.9 g in terms of TiO2) were added under stirring. The resulting mixed solution had a molar ratio of tetraethylammonium hydroxide / titanium atom of 1.00 and a molar ratio of glycine / titanium atom of 0.70. After the mixed solution was kept at 90°C for 2 hours, it was kept at 95°C for 5 hours to prepare a titanium mixed solution. The pH of the modulated titanium mixed solution was 11.1, and the TiO2 concentration was 3.0% by mass. 1500 g of the above titanium mixed solution was placed in a 3-liter SUS autoclave container and hydrothermally treated at 150°C for 5 hours. After cooling to room temperature, the hydrothermally treated solution taken out was an aqueous dispersion of milky white titanium oxide colloidal particles. The obtained dispersion had a pH of 12.2, a TiO2 concentration of 3.0% by mass, and an average particle size (dynamic light scattering particle size) obtained by dynamic light scattering (DLS) of 140 nm.
[0263] (Production Example 4: Preparation of Titanium Oxide Colloidal Particles (C4) Modified with Silica-Tin Oxide Composite Oxide)
[0264] 247.1 g of the alkaline silica-tin oxide composite oxide colloidal particles (B1) prepared in Reference Example 2 were added to 1400.0 g of the aqueous dispersion sol of the titanium oxide colloidal particles (A4) obtained in Reference Example 5 under stirring. The mixture was then heated to 95° C. and maintained for 2 hours, and then passed through a column filled with a hydrogen-type cation exchange resin (Anvaliate (registered trademark) IR-120B). The sol after passing through the column was concentrated by ultrafiltration to obtain an aqueous dispersion sol of titanium oxide colloidal particles (C4) modified with silica-tin oxide composite oxide. The aqueous dispersion sol had a total metal oxide (TiO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 3.5 mPa·s, and an average particle size (dynamic light scattering particle size) of 128 nm as determined by a dynamic light scattering method (DLS).
[0265] (Example 1)
[0266] To 100 g of the water-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide obtained in Production Example 1, 69.5 g of IPA (isopropyl alcohol) and 1.52 g of polyoxyethylene alkyl ether phosphate (Toho Chemical Industry Co., Ltd.: trade name RA-600) were added under stirring to modify the surface of the particles. Next, the dispersion medium of the obtained water-dispersed sol was replaced with IPA using a rotary evaporator to obtain an IPA-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide. At this stage, the methanol remaining in the solvent was reduced. The IPA dispersed sol had a pH of 5.0, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 20.5% by mass, a viscosity of 2.3 mPa·s, and an average particle size (dynamic light scattering particle size) of 22 nm as determined by dynamic light scattering (DLS). The metal oxide particles contained 11.4 mol% SnO2, 54.8 mol% TiO2, 10.1 mol% ZrO2, and 23.6 mol% SiO2.
[0267] At this time, the amount of methanol remaining in the composition as methanol in the dispersion medium was 11 ppm, and the amount of formaldehyde before and after the light resistance test was less than 1 ppm, respectively.
[0268] (Example 2)
[0269] In Example 1, the sol was prepared in the same manner as in Example 1 except that the solvent was changed to propylene glycol monomethyl ether (PGME). At this time, the PGME dispersed sol had a pH of 4.2, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 4.5 mPa·s, and an average particle size (dynamic light scattering particle size) obtained by dynamic light scattering (DLS) of 26 nm. The metal oxide particles contained 11.4 mol% of SnO2, 54.8 mol% of TiO2, 10.1 mol% of ZrO2, and 23.6 mol% of SiO2.
[0270] At this time, the methanol in the composition was 10 ppm as methanol in the dispersion medium, and the amount of formaldehyde before and after the light resistance test was less than 1 ppm.
[0271] (Example 3)
[0272] 30.5 g of a 5% citric acid aqueous solution was added to 100 g of the water-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silica-tin oxide composite oxide obtained in Production Example 1 under stirring. Next, the sol was heated at 90° C. for 2 hours to modify the surface of the particles with citric acid. The dispersion medium of the obtained water-dispersed sol was replaced with n-propanol using a rotary evaporator to obtain a n-propanol-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silica-tin oxide composite oxide. In this step, the methanol remaining in the solvent was reduced. The n-propanol-dispersed sol had a pH of 3.5, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 19.5% by mass, a viscosity of 2.2 mPa·s, and an average particle size (dynamic light scattering method particle size) of 18 nm as obtained by dynamic light scattering (DLS). The metal oxide particles contain 11.4 mol % of SnO 2 , 54.8 mol % of TiO 2 , 10.1 mol % of ZrO 2 , and 23.6 mol % of SiO 2 .
[0273] At this time, the methanol in the composition was 5 ppm as methanol in the dispersion medium, and the amount of formaldehyde before and after the light resistance test was less than 1 ppm.
[0274] (Example 4)
[0275] In Example 1, the same method as in Example 1 was used except that the sol was changed to the zirconium oxide-tin oxide composite oxide colloidal particles (C2) modified with the silicon dioxide-tin oxide composite oxide of Production Example 2. The obtained IPA dispersed sol had a pH of 5.0, a total metal oxide (ZrO2, SnO2, and SiO2) concentration of 20.3% by mass, a viscosity of 2.2 mPa·s, and an average particle size (dynamic light scattering particle size) obtained by dynamic light scattering (DLS) of 27 nm. The content of SnO2 in the metal oxide particles was 11.8 mol%, that of ZrO2 was 67.2 mol%, and that of SiO2 was 20.9 mol%.
[0276] At this time, the methanol in the composition was 10 ppm as methanol in the dispersion medium, and the amount of formaldehyde before and after the light resistance test was less than 1 ppm.
[0277] (Example 5)
[0278] In Example 1, the same method as in Example 1 was used except that the sol was changed to the tin oxide colloidal particles (C3) modified with the silica-tin oxide composite oxide of Production Example 3. The obtained IPA dispersed sol had a pH of 5.0, a total metal oxide (SnO2 and SiO2) concentration of 20.5% by mass, a viscosity of 2.5 mPa·s, and an average particle size (dynamic light scattering particle size) obtained by dynamic light scattering (DLS) of 26 nm. The SnO2 content in the metal oxide particles was 80.7 mol%, and the SiO2 content was 19.3 mol%.
[0279] At this time, the methanol in the composition was 10 ppm as methanol in the dispersion medium, and the amount of formaldehyde before and after the light resistance test was less than 1 ppm.
[0280] (Example 6)
[0281] To 100 g of the water-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide obtained in Production Example 1, 1.53 g of a polyether-modified silane (manufactured by Shin-Etsu Chemical Co., Ltd.: trade name X-12-641, structure: (CH3O)3SiC3H6(OC2H4)nOCH3) was added under stirring. Then, the sol was heated at 70°C for 5 hours to modify the surface of the particles. The dispersion medium of the obtained water-dispersed sol was replaced with n-propanol using a rotary evaporator to obtain a n-propanol-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide. In this stage, the methanol remaining in the solvent was reduced. The n-propanol dispersed sol had a pH of 6.9, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.5% by mass, a viscosity of 4.6 mPa·s, and an average particle size (dynamic light scattering particle size) of 15 nm as determined by dynamic light scattering (DLS). The metal oxide particles contained 11.4 mol% SnO2, 54.8 mol% TiO2, 10.1 mol% ZrO2, and 23.6 mol% SiO2.
[0282] At this time, the methanol in the composition was 5 ppm as methanol in the dispersion medium, and the amount of formaldehyde before and after the light resistance test was less than 1 ppm.
[0283] (Example 7)
[0284] Methanol was added to the n-propanol dispersion sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide obtained in Example 6 so that the methanol in the composition was the methanol in the dispersion medium and the residual methanol content was 25 ppm in the experiment. The content of SnO2 in the metal oxide particles was 11.4 mol%, that of TiO2 was 54.8 mol%, that of ZrO2 was 10.1 mol%, and that of SiO2 was 23.6 mol%.
[0285] The formaldehyde content of the n-propanol dispersion sol before and after the light resistance test was less than 1 ppm.
[0286] (Example 8)
[0287] Methanol was added to the n-propanol dispersion sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide obtained in Example 6 so that the methanol in the composition was the methanol in the dispersion medium and the residual methanol content was 50 ppm in the experiment. The content of SnO2 in the metal oxide particles was 11.4 mol%, that of TiO2 was 54.8 mol%, that of ZrO2 was 10.1 mol%, and that of SiO2 was 23.6 mol%.
[0288] The formaldehyde content of the n-propanol dispersion sol before and after the light resistance test was less than 1 ppm.
[0289] (Example 9)
[0290] Methanol was added to the n-propanol dispersion sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide obtained in Example 6 so that the methanol in the composition was the methanol in the dispersion medium and the residual methanol content was 75 ppm in the experiment. The content of SnO2 in the metal oxide particles was 11.4 mol%, that of TiO2 was 54.8 mol%, that of ZrO2 was 10.1 mol%, and that of SiO2 was 23.6 mol%.
[0291] The formaldehyde content of the n-propanol dispersion sol before and after the light resistance test was less than 1 ppm.
[0292] (Example 10)
[0293] Methanol was added to the n-propanol dispersion sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silicon dioxide-tin oxide composite oxide obtained in Example 6 so that the methanol in the composition was the methanol in the dispersion medium and the residual methanol content was 100 ppm in the experiment. The content of SnO2 in the metal oxide particles was 11.4 mol%, that of TiO2 was 54.8 mol%, that of ZrO2 was 10.1 mol%, and that of SiO2 was 23.6 mol%.
[0294] The formaldehyde content of the n-propanol dispersion sol before and after the light resistance test was less than 1 ppm.
[0295] (Example 11)
[0296] To 100 g of the water-dispersed sol of titanium oxide colloidal particles (C4) modified with silica-tin oxide composite oxide obtained in Production Example 4, 69.3 g of IPA and 1.53 g of polyoxyethylene alkyl ether phosphate (RA-600 manufactured by Toho Chemical Industry Co., Ltd.) were added under stirring to modify the surface of the particles. Next, the dispersion medium of the obtained water-dispersed sol was replaced with IPA using a rotary evaporator to obtain an IPA-dispersed sol of titanium oxide colloidal particles (C4) modified with silica-tin oxide composite oxide. The IPA-dispersed sol had a pH of 2.9, a total metal oxide (TiO2, SnO2, and SiO2) concentration of 20.5% by mass, a viscosity of 9.1 mPa·s, and an average particle size (dynamic light scattering method particle size) of 375 nm obtained by dynamic light scattering (DLS). The metal oxide particles contained 1.6 mol% of SnO2, 90.4 mol% of TiO2, and 8.0 mol% of SiO2.
[0297] At this time, the methanol in the composition was 9 ppm as methanol in the dispersion medium, and the amount of formaldehyde before and after the light resistance test was less than 1 ppm.
[0298] (Comparative Example 1)
[0299] 100 g of the water-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silica-tin oxide composite oxide obtained in Production Example 1 was replaced with methanol using a rotary evaporator to obtain a methanol-dispersed sol of the titanium oxide-tin oxide-zirconium oxide composite oxide colloidal particles (C1) modified with the silica-tin oxide composite oxide. The methanol-dispersed sol had a pH of 6.0, a total metal oxide (TiO2, ZrO2, SnO2, and SiO2) concentration of 30.0% by mass, a viscosity of 1.4 mPa·s, and an average particle size (dynamic light scattering particle size) of 18 nm as determined by a dynamic light scattering method (DLS). The metal oxide particles contained 11.4 mol% of SnO2, 54.8 mol% of TiO2, 10.1 mol% of ZrO2, and 23.6 mol% of SiO2.
[0300] At this time, the methanol in the composition was 70% as methanol in the dispersion medium, and the formaldehyde content before the light resistance test was less than 1 ppm, but the formaldehyde content after the light resistance test was 25 ppm.
[0301] (Comparative Example 2)
[0302] In Comparative Example 1, the dispersion medium was changed to ethanol, and the same procedure as in Comparative Example 1 was followed. The metal oxide particles contained 11.4 mol % of SnO 2 , 54.8 mol % of TiO 2 , 10.1 mol % of ZrO 2 , and 23.6 mol % of SiO 2 .
[0303] At this time, the amount of ethanol remaining in the composition as ethanol in the dispersion medium was 70%, the amount of acetaldehyde before the light resistance test was 3 ppm, and the amount of acetaldehyde after the light resistance test was 25 ppm.
[0304] (Comparative Example 3)
[0305] In Example 1, the same procedure as in Example 1 was carried out except that polyoxyethylene alkyl ether phosphate (RA-600 manufactured by Toho Chemical Industry Co., Ltd.) was not added. At this time, the sol was gelled during the solvent replacement and was not dispersed in IPA.
[0306] (Comparative Example 4)
[0307] In Example 2, the same method as in Example 2 was used except that 1.22 g of 3-methacryloxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-503) was used instead of polyoxyethylene alkyl ether phosphate (manufactured by Toho Chemical Industry Co., Ltd.: RA-600). The content of SnO2 in the metal oxide particles was 11.4 mol%, that of TiO2 was 54.8 mol%, that of ZrO2 was 10.1 mol%, and that of SiO2 was 23.6 mol%.
[0308] At this time, the methanol in the composition was 400 ppm as methanol in the dispersion medium, the formaldehyde amount before the light resistance test was less than 1 ppm, and the formaldehyde amount after the light resistance test was 7 ppm.
[0309] (Comparative Example 5)
[0310] In Comparative Example 1, the same method as in Comparative Example 1 was used except that the sol was changed to zirconium oxide-tin oxide composite oxide colloidal particles (C2) modified with silicon dioxide-tin oxide composite oxide in Production Example 2. The metal oxide particles contained 11.8 mol % of SnO2, 67.2 mol % of ZrO2, and 20.9 mol % of SiO2.
[0311] At this time, the methanol in the composition was 70% as methanol in the dispersion medium, the formaldehyde content before the light resistance test was less than 1 ppm, and the formaldehyde content after the light resistance test was 2 ppm.
[0312] (Comparative Example 6)
[0313] In Comparative Example 1, the same procedures as in Comparative Example 1 were performed except that the sol was changed to the tin oxide colloidal particles (C3) modified with the silica-tin oxide composite oxide of Production Example 3. The content of SnO2 in the metal oxide particles was 80.7 mol % and the content of SiO2 was 19.3 mol %.
[0314] At this time, the methanol in the composition was 70% as methanol in the dispersion medium, the formaldehyde content before the light resistance test was less than 1 ppm, and the formaldehyde content after the light resistance test was 12 ppm.
[0315] The sols prepared in Examples 1 to 10 all showed excellent stability without gelation or phase separation. Furthermore, it was confirmed that the generation of formaldehyde due to the photocatalytic activity of the particles was less than 1 ppm regardless of ultraviolet irradiation, showing excellent light resistance.
[0316] On the other hand, the compositions of Comparative Examples 1, 2, 5, and 6 contained more methanol and ethanol than the Examples, and formaldehyde and acetaldehyde were generated in the light resistance test. Comparative Example 3 had poor dispersibility in IPA due to the lack of surface modification of particles. The composition of Comparative Example 4 contained more residual methanol than Example 10, and formaldehyde was generated in the light resistance test.
[0317] Industrial Availability
[0318] A composition comprising photoactive metal oxide particles and capable of suppressing the generation of aldehyde compounds and the like even by photocatalytic action, and a method for producing the same, thereby suppressing the generation of harmful volatile aldehyde compounds.
Claims
1. A composition comprising photoactive metal oxide particles (A), a dispersant (B), and an organic solvent (C) other than a volatile aldehyde compound, wherein the alcohol having 1 to 2 carbon atoms contained in the composition is at a ratio of 200 ppm or less, and the photoactive metal oxide particles (A) are metal oxide particles having an average particle size of 5 to 500 nm as measured by a dynamic light scattering method, The photoactive metal oxide particles (A) contain 50 mol % or more of at least one photoactive metal oxide selected from titanium oxide, tin oxide, and zirconium oxide in all metal oxides. The composition has a solid content of 0.1 to 70% by mass, and the photoactive metal oxide particles (A) account for 80 to 99% by mass and the dispersant (B) accounts for 1 to 20% by mass of the total solid content.
2. The composition according to claim 1, wherein the photoactive metal oxide particles (A) are metal oxide particles formed of a photoactive metal oxide, metal oxide particles containing a photoactive metal oxide, or core-shell metal oxide particles, The core-shell type metal oxide particles are core-shell type metal oxide particles in which the surface of the metal oxide particle to be the core is coated with a coating layer of a metal oxide particle having a metal oxide component or a metal oxide content different from that of the metal oxide of the core. The metal oxide particles of the core, the metal oxide particles of the coating layer, or both contain a photoactive metal oxide.
3. The composition according to claim 2, wherein the photoactive metal oxide particles (A) are core-shell type metal oxide particles in which the surfaces of metal oxide particles containing titanium oxide as cores are coated with metal oxide particles containing silicon dioxide, and the metal oxide particles contain 50 mol % or more of titanium oxide in the total metal oxide.
4. The composition according to claim 2, wherein the metal oxide particles of the core are particles of titanium oxide, zirconium oxide, tin oxide, a composite oxide of titanium oxide and tin oxide, a composite oxide of zirconium oxide and tin oxide, a composite oxide of titanium oxide and zirconium oxide, or a composite oxide of titanium oxide, zirconium oxide and tin oxide. 5 . The composition according to claim 2 , wherein the metal oxide particles of the coating layer are particles of at least one metal oxide selected from the group consisting of silicon dioxide, tin oxide, antimony oxide, tungsten oxide, aluminum oxide, and zirconium oxide, or particles of a composite metal oxide. 6 . The composition according to claim 1 , wherein the dispersant (B) is a silane compound, an organic acid or a salt thereof, a phosphoric acid ester, or a surfactant.
7. The composition according to claim 6, wherein the silane compound is a silane coupling agent, and the silane coupling agent is at least one silane compound selected from formula (1) to formula (3), R 1 a Si(R 2 ) 4-a formula(1) 〔R 3 b Si(R 4 ) 3-b 〕2Y c Formula (2) R 5 d Si(R 6 ) 4-d formula(3) In formula (1), R 1 Each of R 1 Combined with silicon atoms by Si-C bonds, R 2 Each represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer of 1 to 3. In formula (2) and formula (3), R 3 and R 5 Each of them is an alkyl group having 1 to 3 carbon atoms or an aryl group having 6 to 30 carbon atoms, and R 3 and R 5 Each is bonded to the silicon atom by Si-C bond, R 4 and R 6 Each represents an alkoxy group, an acyloxy group, or a halogen group, Y represents an alkylene group, an NH group, or an oxygen atom, b is an integer of 1 to 3, c is an integer of 0 or 1, and d is an integer of 1 to 3.
8. The composition according to claim 6, wherein the organic acid is at least one organic acid selected from the group consisting of dibasic aliphatic carboxylic acids, aliphatic hydroxycarboxylic acids, amino acids, and chelating agents, wherein the dibasic aliphatic carboxylic acids are selected from the group consisting of oxalic acid, malonic acid, and succinic acid, the aliphatic hydroxycarboxylic acids are selected from the group consisting of glycolic acid, lactic acid, malic acid, tartaric acid, and citric acid, the amino acids are selected from the group consisting of glycine, alanine, valine, leucine, serine, and threonine, and the chelating agents are selected from the group consisting of ethylenediaminetetraacetic acid, L-aspartic acid-N,N-diacetic acid, and diethylenetriaminepentaacetic acid.
9. The composition according to claim 6, wherein the phosphate ester is at least one phosphate ester selected from the group consisting of formula (4) to formula (6), In formulae (4) to (6), X1, X2, and X3 each represent an alkylene group having 2 to 20 carbon atoms, f, h, and j each represent an integer from 1 to 100, e, g, and i each represent an integer from 1 to 3, and Y1, Y2, and Y3 each represent a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, or a (meth)acryloyl group. 10 . The composition according to claim 6 , wherein the phosphoric acid ester is a polyoxyethylene C 6-10 alkyl ether phosphoric acid ester having an alkyl group having 6 to 10 carbon atoms.
11. The composition according to claim 6, wherein the surfactant is an anionic surfactant, a cationic surfactant, a nonionic surfactant, or an amphoteric surfactant. 12 . The composition according to claim 1 , wherein the organic solvent (C) is an alcohol, ester, ketone, amide, or hydrocarbon having 3 to 10 carbon atoms and optionally having an ether bond.
13. The composition according to claim 1 or 2, further comprising a secondary or tertiary amine having a total carbon number of 5 to 35.
14. The composition according to claim 1 or 2, at 0.4 mW / cm 2 When 15 g of the composition was irradiated with ultraviolet rays having a wavelength of 365 nm at an intensity of 100 nm for 4 hours, the volatile aldehyde compound generated in the composition was 2 ppm or less. 15 . A varnish comprising the composition according to claim 1 and further comprising a thermosetting or photocurable resin.
16. The varnish according to claim 15, which is a hard coating agent or a filler.
17. The method for producing the composition according to any one of claims 1 to 14, comprising the following steps (i) and (ii): Step (i): a step of mixing photoactive metal oxide particles (A), a dispersant (B), and an organic solvent (C) other than a volatile aldehyde compound, Step (ii): a step (ii) of removing the alcohol having 1 to 2 carbon atoms in the liquid obtained in step (i) until the alcohol having 1 to 2 carbon atoms is contained in the entire solvent in a proportion of 200 ppm or less.
Citation Information
Patent Citations
Titanium oxide dispersion liquid
JP2011074328A
Silane surface-treated metal oxide fine particles and production method for same.
WO2011090084A1
Method of manufacturing surface-modified metal oxide fine particle, method of manufacturing modified metal oxide fine particle, surface-modified metal oxide fine particle, and metal oxide fine particle-dispersed liquid
JP2020075854A
Metal oxide particles containing titanium oxide coated with silicon dioxide-stannic oxide complex oxide
US20140199554A1